Prenatally diagnosed large intrapericardial rhabdomyoma without haemodynamic compromise - Atiq, Mehnaz; Durre Shahwar; Kashif Abbas Zaidi (Journal of the Pakistan Medical Association, 2022)
Cardiac rhabdomyoma is the most common primary cardiac tumour and is considered to be a hamartoma of developing embryonic cardiac myocytes. It is commonly seen in tuberous sclerosis. The size and location of the tumour is the surrogate determinant of the risk of haemodynamic compromise. Pericardial rhabdomyoma is very rare and tends to follow the inherent natural history of spontaneous regression. We present cases of two foetuses diagnosed with large pericardial rhabdomyoma and no haemodynamic consequences. Key Words: Fetal cardiac tumors, intrapericardial rhabdomyoma, prenatal diagnosis.